2017
DOI: 10.1016/s2095-3119(16)61546-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of kiwifruit firmness using fruit mineral nutrient concentration by artificial neural network (ANN) and multiple linear regressions (MLR)

Abstract: Many properties of fruit are influenced by plant nutrition. Fruit firmness is one of the most important fruit characteristics and determines post-harvest life of the fruit. In recent decades, artificial intelligence systems were employed for developing predictive models to estimate and predict many agriculture processes. In the present study, the predictive capabilities of multiple linear regressions (MLR) and artificial neural networks (ANNs) are evaluated to estimate fruit firmness in sixth months, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 30 publications
1
52
0
2
Order By: Relevance
“…Such results show the suitability of use of neural networks for yield prediction in lima bean. Niazian et al (2018), using metrics similar to those presented here, observed the efficiency of the ANN tool compared to the MLR model to predict seed yield of ajowan, and Torkashvand et al (2017) observed the superiority of MLR models over ANNs using the RMSE and correlation measures applied to observed and predicted data. Niedbała et al (2019) used the MAE and MAPE measures to evaluate the relative efficiency of three artificial neural network architectures.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Such results show the suitability of use of neural networks for yield prediction in lima bean. Niazian et al (2018), using metrics similar to those presented here, observed the efficiency of the ANN tool compared to the MLR model to predict seed yield of ajowan, and Torkashvand et al (2017) observed the superiority of MLR models over ANNs using the RMSE and correlation measures applied to observed and predicted data. Niedbała et al (2019) used the MAE and MAPE measures to evaluate the relative efficiency of three artificial neural network architectures.…”
Section: Resultssupporting
confidence: 58%
“…In recent years, artificial intelligence has repeatedly been used to predict the phenotypic expression of agronomic traits in economically important species, or even in species with high economic potential. Torkashvand et al (2017) used Multilayer perceptrons (MLPs) to predict fruit firmness in kiwi varieties AMCB Sousa et al…”
Section: Introductionmentioning
confidence: 99%
“…Considering that firmness is one of the most important properties of fresh fruits, and is highly connected with shelf-life, Torkashvand et al [2] used ANN models to develop predictive methods for fruit firmness of kiwis. Their results seemed to indicate that the ANN model showed better potential in determining the relationship between firmness and nutrients concentration, when compared to the predictive capacity of multiple linear regression.…”
Section: B Texture and Rheologymentioning
confidence: 99%
“…ANNs correspond to computational systems that aim to imitate some properties of biological neurons. Methods based on ANNs imitate the natural neural system via computer programs being fairly popular due to several advantages such as, for example: nonlinearity, adaptation, generalization, model independence, easy to use and high accuracy [1], [2]. The first artificial model of a biological neuron was obtained in 1943 by the pioneering work of Warren McCulloch (psychiatrist and neuroanatomist) and Walter Pitts (mathematician).…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, much attention has recently been focused on the nonparametric-based methods in the degradation prognostic of rotating machinery. For instance, artificial neural network (ANN) [17][18][19][20], fuzzy logic [21], and deep learning network (DPN) [22,23], etc., could be considered as successful nonparametric-based approaches in the PHM field. The benefit of using nonparametric-based methods lies in their ability to model the evolution of complex multi-dimensional degradation data, which can effectively extract latent features such as the spatio-temporal correlations (STC) among historical data.…”
Section: Of 27mentioning
confidence: 99%